2022
DOI: 10.18311/mvpjms/2021/v8i2/281
|View full text |Cite
|
Sign up to set email alerts
|

Double J Stenting - Clinical Profile, Indications and Post Operative Complications

Abstract: Introduction: Ureteric stents have become one of the most basic and valuable tools in the urological practice. Indwelling ureteral stents provide direct drainage of the upper urinary tract to the bladder without the need for external diversion. The indications for insertion of stents into the urinary tract has expanded significantly during the last decade. However, their use is not free of complications and problems. The present study was designed to observe the clinical profile of patients presenting with obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
2
0
0
1
Order By: Relevance
“…The occurrence of complications such as painful trigone irritation post-DJS and bleeding post-PCN highlights the material-dependent mechanical limitations of ureteral stents. The frequencies of these complications in our study are consistent with those reported in the literature, underscoring the importance of anticipating and managing such adverse effects (16,17,18,19). The rates of septicemia following DJS and PCN in our study also align with previously reported figures, further emphasizing the need for vigilant postprocedural monitoring and management (2,17,18,20).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The occurrence of complications such as painful trigone irritation post-DJS and bleeding post-PCN highlights the material-dependent mechanical limitations of ureteral stents. The frequencies of these complications in our study are consistent with those reported in the literature, underscoring the importance of anticipating and managing such adverse effects (16,17,18,19). The rates of septicemia following DJS and PCN in our study also align with previously reported figures, further emphasizing the need for vigilant postprocedural monitoring and management (2,17,18,20).…”
Section: Discussionsupporting
confidence: 90%
“…The frequencies of these complications in our study are consistent with those reported in the literature, underscoring the importance of anticipating and managing such adverse effects (16,17,18,19). The rates of septicemia following DJS and PCN in our study also align with previously reported figures, further emphasizing the need for vigilant postprocedural monitoring and management (2,17,18,20). This investigation underlines the effectiveness and safety of ultrasound-guided percutaneous nephrostomy as a superior method for temporary urine diversion in obstructive uropathy, especially in cases complicated by malignant diseases.…”
Section: Discussionsupporting
confidence: 90%
“…Keluhan dirasakan pada pinggang bawah dan pada saat buang air kecil (Glavinov et al, 2022). Double J stent memang diketahui menyebabkan ketidaknyamanan dan rasa sakit pada lebih dari 90% pasien, terutama dirasakan pada area pinggang dan suprapubik yang mengganggu kehidupan sehari-hari pasien yang menggunakan stent (Mogal et al, 2022). Hal ini disebabkan pemasangan stent dapat menyebabkan pergeseran ke arah ginjal karena efek peristaltik ureter (Ramachandra et al, 2020).…”
Section: Pembahasan Nyeriunclassified